Toward a Routine Assessment of Visceral Adipose Tissue Volume from Computed Tomographic Data. Issue 2 (25th December 2020) - Schaudinn, Alexander; Hudak, Andrea; Linder, Nicolas; Reinhardt, Martin; Stocker, Gertraud; Lordick, Florian; Denecke, Timm; Busse, Harald
Abstract : Objective: The study's aim was to determine to what extent total visceral adipose tissue (VAT) volume ( V VAT‐T ) measured from segmented VAT areas ( A VAT ) on all axial computed tomography (CT) sections (thickness of 5 mm) between the diaphragm and pelvic floor can be predicted by the A VAT of commonly selected landmark sections in patients with overweight or obesity. Methods: A total of 113 patients (31 females, 82 males) with images of full abdominopelvic coverage and proper image quality were included (BMI = 25.0‐64.1 kg/m 2, 29.5 ± 4.9 kg/m 2 ). Linear regression between A VAT and V VAT‐T (reference) was used to determine approximate equations for VAT volume for all parameters (single sex, different anatomical landmarks or lumbar intervertebral disc spaces, one or five axial sections). Agreement was evaluated by the multivariate coefficient of determination and by the SD of the percentage difference ( s d% ) between the estimated VAT volume on one or five sections and V VAT‐T . Results: The V VAT‐T was 0.9 to 8.4 (3.8 ± 2.2) L for females and 2.7 to 11.7 (5.6 ± 2.1) L for males. Best agreement was found at L2‐3 ( s d%  = 14.3%‐15.5%) for females and at L1‐2 or L2‐3 (11.7%‐12.4%) for males. Agreement at the umbilicus or the femoral heads was poor (20.2%‐57.9%). Segmentation of one or five sections was substantially faster (11/70 seconds) than whole‐abdomen processing (15 minutes). Conclusions: V VAT‐T can be rapidly estimated by VAT segmentation of axial CT sections at sex‐specific lumbar intervertebral disc spaces.